Pengaruh Iklan Dan Duta Merek Terhadap Keputusan Pembelian Pada Pelanggan Shopee - Tri Cahyono, Edhy; Syahril, Megawati (GEMA EKONOMI, 2023)
With the rapid development of information technology, online shopping platforms have sprung up to facilitate changes in consumer behavior that are starting to shop online. In communicating superiority and attracting customer interest to use the online shopping platform, advertising media and brand ambassadors are massively used to carry out marketing campaigns. The purpose of this study was to determine the effect of advertising and selecting brand ambassadors on the purchasing decisions of Shopee customers, one of the fastest growing online shopping platforms. This research is a quantitative research with a correlational approach with regression analysis to see the relationship between variables. Data collection techniques were carried out using a questionnaire. This study has three (3) variables, namely Advertising and Brand Ambassadors as independent variables and Purchase Decision as the dependent variable. The subjects in this study were 100 students in the Province of D.I.Y who had shopped online using the Shopee platform. From the processing of the research results, it was concluded that advertising has a positive influence on purchasing decisions, and brand ambassadors have no effect on purchasing decisions of Shopee consumers from DIY students.